2018
DOI: 10.5125/jkaoms.2018.44.4.174
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for outcome of surgical treatment in medication-related osteonecrosis of the jaw

Abstract: ObjectivesThe number of patients with medication-related osteonecrosis of the jaw (MRONJ) is increasing, but treatment remains controversial. Published papers and systematic reviews have suggested that surgical treatment is effective in patients with MRONJ. The purpose of this study was to determine whether preoperative University of Connecticut Osteonecrosis Numerical Scale (UCONNS), other serologic biomarkers, and size of necrosis are prognostic factors for outcome of surgical treatment in MRONJ.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
5
9
0
1
Order By: Relevance
“…In an earlier study, we assessed the prognosis of ONJ in osteoporotic patients receiving oral alendronate and found that lesion depth ≦10 mm, pretreatment serum bone‐specific alkaline phosphatase (BSAP) level >10 μg/L, and lesions in anterior regions of the mouth denoted a better healing within 6 months (Lee et al., 2013). Recently, a Korean group reported that C‐reactive protein (CRP), University of Connecticut Osteonecrosis Numerical Scale (UCONNS), and serum alkaline phosphatase (ALP) were key factors in predicting the prognosis of 52 patients with MRONJ who underwent surgery, regardless of drug types and therapeutic indications (Shin & Kim, 2018). Because the disease nature and formulations of antiresorptive drugs for bone malignancy are different from those of osteoporosis, prognosis of MRONJ in oncologic patients needs to be considered separately.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, we assessed the prognosis of ONJ in osteoporotic patients receiving oral alendronate and found that lesion depth ≦10 mm, pretreatment serum bone‐specific alkaline phosphatase (BSAP) level >10 μg/L, and lesions in anterior regions of the mouth denoted a better healing within 6 months (Lee et al., 2013). Recently, a Korean group reported that C‐reactive protein (CRP), University of Connecticut Osteonecrosis Numerical Scale (UCONNS), and serum alkaline phosphatase (ALP) were key factors in predicting the prognosis of 52 patients with MRONJ who underwent surgery, regardless of drug types and therapeutic indications (Shin & Kim, 2018). Because the disease nature and formulations of antiresorptive drugs for bone malignancy are different from those of osteoporosis, prognosis of MRONJ in oncologic patients needs to be considered separately.…”
Section: Introductionmentioning
confidence: 99%
“…Debridement was chosen as single therapy in 83% of cases, 17% of cases were further treated with wider resections. Shin obtained complete healing with surgical therapy in 63.5% and a lack of closure in 36.5% of cases [64].…”
Section: Discussionmentioning
confidence: 96%
“…Currently, increasing number of patients with MRONJ has been reported in recent years [8][9][10][11][12][13][14][15][16][17] . However, there is no general consensus for treatment of MRONJ, and it is still controversial.…”
Section: Discussionmentioning
confidence: 99%